Estimation of different factors influence on project risk management in small and mediumsized businesses - Doszhan, R. D. (Journal of Economic Research & Business Administration, 2016)
Risk management is an extremely important element among the activities of small and medium-sized enterprises. It is necessary for small and medium-sized enterprises to be able to effectively manage risks to survive in highly competitive and post-crisis era conditions. In the article there were interviewed 82 representatives of small and medium-sized businesses and analyzed the collected data by using empirical method. Assessment of regression equations that determine the presence or absence of small businesses risk management systems was also analyzed, as well as how it changes risk related behavior.